SegNema: Nematode segmentation strategy in digital microscopy images using deep learning and shape models - Jiménez-Chavarría, José (Instituto Tecnológico de Costa Rica, 2019)
Nematodes are the most numerous multicellular animals on Earth and their study has a direct impact in the improvement and development of agricultural activities. This document introduces SegNema, a strategy for the segmentation of nematodes in microscopy images where deep learning is used for classification of pixels as nematode or background, and a shape model is used to associate landmarks that describe the position of the nematode in the image. To train the segmentation model, a set of 2939 manually labeled uncompressed images of size 1024 ⇥ 768 pixels obtained from 13 di↵erent sequences of microscopy images is used. The landmarks that describe the position of the nematodes in these training images are used to adjust a model capable of representing shapes corresponding to a nematode. The disparity between the shapes of the regions classified as nematode in the segmentation stage and their possible truncated representation with the shape model is used to rule out possible erroneous classifications. The validation of this model was performed on 321 images of the microscopy sequences that were not used in the training stage. In each image used for training and validation, there is information on the position of landmarks where a single nematode is delimited although more nematodes may be present.

Los nematodos son los animales pluricelulares más numerosos en la Tierra y su estudio tiene un impacto en el desarrollo de actividades agrícolas. En este documento se introduce SegNema, una estrategia para la segmentación de nematodos en imágenes de microscopia donde se utiliza aprendizaje profundo para clasificación de píxeles como nematodo o fondo, y modelos de forma para asociar hitos que describen la posición del nematodo en la imagen. Para entrenar el modelo de segmentación se usan 2939 imágenes sin comprimir etiquetadas manualmente de tamaño 1024 ⇥ 768 p´ıxeles obtenidas de 13 secuencias de imágenes de microscopia. Por otro lado, los hitos que describen la posición de los nematodos en estas imágenes de entrenamiento son utilizados para ajustar un modelo capaz de representar formas correspondientes a nematodo. La disparidad entre formas de las regiones clasificadas como nematodo en la etapa de segmentación y su posible representación truncada con el modelo de forma es usado para descartar posibles clasificaciones err´oneas. Para la validación de este modelo se usan 321 imágenes de las secuencias de microscopia que no son utilizadas en la etapa de entrenamiento. En cada imagen usada para entrenamiento y validación existe la información de la posici´on de hitos donde se delimita un único nematodo aunque otros nematodos pueden estar presentes.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2019.
Keywords: Research Subject Categories::TECHNOLOGY::Information technology::Computer engineering; Nematodos; Microscopia electrónica; Imágenes; Clasificación; Machine learning; Segmentación; Deep Learning; Aprendizaje profundo; Aprendizaje automático; Machine Learning